Recovery from Cranial Nerve Symptoms after Flow Diversion without Coiling for Unruptured Very Large and Giant ICA Aneurysms - Lee, J.K.; Choi, J.H.; Kim, B.-S.; Shin, Y.S. (American Journal of Neuroradiology, 2022)
BACKGROUND AND PURPOSE: Cranial nerve symptoms, including visual impairment and ophthalmoplegia, are one of the most common presentations of very large and giant (≥15 mm) ICA aneurysms. In this study, we evaluated the treatment outcomes of flow diversion and conventional coiling in terms of recovery from cranial nerve symptoms and postoperative complications.MATERIALS AND METHODS: Seventy-nine patients with unruptured ICA aneurysms of >15 mm who were treated with flow diversion or conventional coiling between December 2009 and December 2020 were retrospectively evaluated. We compared the radiologic and clinical outcomes, including recovery from cranial nerve symptoms, between the 2 groups.RESULTS: Twenty-eight of 49 patients (57.1%) treated with flow diversion and 10 of 30 patients (33.3%) treated with conventional coiling initially presented with cranial nerve symptoms (P = .068). In the clinical follow-up, the symptom recovery rate was significantly higher in those treated with flow diversion (15 [50%] versus 3 [25%] with conventional coiling, P = .046). Multivariate logistic regression analysis demonstrated that flow diversion was significantly associated with symptom recovery (OR, 7.425; 95% CI, 1.091–50.546; P = .040). The overall postoperative complication rate was similar (flow diversion, 10 [20.4%]; conventional coiling, 6 [20.0%], P = .965), though fatal hemorrhagic complications occurred only in patients with intradurally located aneurysms treated with flow diversion (4 [8.2%] versus 0 [0.0%] with coiling, P = .108).CONCLUSIONS: Flow diversion without coiling for very large and giant ICA aneurysms yielded a higher rate of recovery from cranial nerve symptoms, but it may be related to an increased hemorrhagic complication rate, especially for intradurally located aneurysms.OKMO’Kelly-Marotta